If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (11z + -2)(10z + 9) = 0 Reorder the terms: (-2 + 11z)(10z + 9) = 0 Reorder the terms: (-2 + 11z)(9 + 10z) = 0 Multiply (-2 + 11z) * (9 + 10z) (-2(9 + 10z) + 11z * (9 + 10z)) = 0 ((9 * -2 + 10z * -2) + 11z * (9 + 10z)) = 0 ((-18 + -20z) + 11z * (9 + 10z)) = 0 (-18 + -20z + (9 * 11z + 10z * 11z)) = 0 (-18 + -20z + (99z + 110z2)) = 0 Combine like terms: -20z + 99z = 79z (-18 + 79z + 110z2) = 0 Solving -18 + 79z + 110z2 = 0 Solving for variable 'z'. Factor a trinomial. (-9 + -10z)(2 + -11z) = 0Subproblem 1
Set the factor '(-9 + -10z)' equal to zero and attempt to solve: Simplifying -9 + -10z = 0 Solving -9 + -10z = 0 Move all terms containing z to the left, all other terms to the right. Add '9' to each side of the equation. -9 + 9 + -10z = 0 + 9 Combine like terms: -9 + 9 = 0 0 + -10z = 0 + 9 -10z = 0 + 9 Combine like terms: 0 + 9 = 9 -10z = 9 Divide each side by '-10'. z = -0.9 Simplifying z = -0.9Subproblem 2
Set the factor '(2 + -11z)' equal to zero and attempt to solve: Simplifying 2 + -11z = 0 Solving 2 + -11z = 0 Move all terms containing z to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + -11z = 0 + -2 Combine like terms: 2 + -2 = 0 0 + -11z = 0 + -2 -11z = 0 + -2 Combine like terms: 0 + -2 = -2 -11z = -2 Divide each side by '-11'. z = 0.1818181818 Simplifying z = 0.1818181818Solution
z = {-0.9, 0.1818181818}
| 24x^2-4x^3=0 | | (X^2+3x)-(x+4)(3x+8)=(3x+8)(x+3) | | (3b-4)-(-5b+3)= | | 2.4/3 | | 5x^2-8x+4=628 | | ln*4+ln*x=ln*7+ln(2x-2) | | 19=17-2x+5x | | 5-2x=3+2x+2 | | 8B+7X=5A | | 7X+8B=5A | | 4x=20+5x | | -1/3m-7=4 | | 0.7+0.05y=0.715 | | x^4-x^3-2x^2= | | 4a+8=11 | | 18(4c-1)-16=70c+18 | | 2x^2-4x+4=628 | | -3-4x=8x-39 | | 5/9(x-32)=25 | | 8x+13=6x-11 | | x+x-2=628 | | 4+x=180-3x | | Xsquared+5x+10=4 | | 5x^2-28x-297=0 | | 2×=(360/4) | | 4x^3-3x^2+1=0 | | 5k-3/5=5 | | 0.85=8+36lnx | | 2x^2+8x-120= | | .60x+.05(18-x)=.10(-79) | | 5x^3+17x^2+16x+4=0 | | 64+36= |